2015
DOI: 10.1172/jci82647
|View full text |Cite
|
Sign up to set email alerts
|

Human prion protein sequence elements impede cross-species chronic wasting disease transmission

Abstract: A r t i c l e A m e n d m e n t s2 5The label for Figure 1E misidentified the prion inoculum administered to the mice depicted. The correct label is below. CJD-inoculatedThe JCI regrets the error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…In one study, the impact of creating a human‐elk chimeric PrP was evaluated (Kurt et al., ). The chimeric PrP was more susceptible to elk and deer CWD prions, but was concurrently less susceptible to human CJD prions (Kurt et al., ). This is consistent with known determinants of inter‐species prion conversion, including PrP C and PrP Sc sequence similarity and the conformation of the infectious prion.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…In one study, the impact of creating a human‐elk chimeric PrP was evaluated (Kurt et al., ). The chimeric PrP was more susceptible to elk and deer CWD prions, but was concurrently less susceptible to human CJD prions (Kurt et al., ). This is consistent with known determinants of inter‐species prion conversion, including PrP C and PrP Sc sequence similarity and the conformation of the infectious prion.…”
Section: Resultssupporting
confidence: 65%
“…The low risk of bias and the consistency of the research conclusions across these studies, despite the use of different lines of transgenic mice, gives this group of studies a *** GRADE indicating that we have some confidence the overall conclusions of this research will not change with future research. In one study, the impact of creating a human‐elk chimeric PrP was evaluated (Kurt et al., ). The chimeric PrP was more susceptible to elk and deer CWD prions, but was concurrently less susceptible to human CJD prions (Kurt et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies focused on the role of specific structural elements during adaptive transspecies transmissions, particularly the loop connecting PrP β2 and α2 regions (22,23), which is disordered in most species but conformationally defined in others such as elk and bank vole PrP C . Although β2-α2 loop rigidity was thought to potentiate PrP C to PrP Sc conversion (24), subsequent studies revealed that PrP C of species considered resistant to prions, including horses, also contained rigid β2-α2 loops (25)(26)(27).…”
Section: Significancementioning
confidence: 99%
“…For the transmission of GSS in bank voles, the peculiar features of the vole PrP amino acid sequence might have been one of these factors. It has been found that the presence of asparagines in or near the β2-α2 loop might create a permissive PrP sequence able to overcome some species barriers, 42 and that recombinant vole PrP with methionine at residue 109 is an apparently universal substrate for RT-QuIC-based in vitro replication of disease-linked PrP Sc isoforms 38 . However, ongoing studies in bank voles carrying methionine instead of isoleucine at residue 109 of PrP (Bv109M) show that, at variance with Bv109I, Bv109M are rather resistant to GSS with 8 kDa PrP res (unpublished data).…”
Section: The Elusive Nature Of the Experimental Transmissibility Of Gssmentioning
confidence: 99%